2019
DOI: 10.1021/acsnano.9b00634
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Alloying Strategy for Exceptional Potassium Ion Batteries

Abstract: We report an in situ alloying strategy for obtaining homogeneous (Bi,Sb) alloy nanoparticles from (Bi,Sb)2S3 nanotubes for the exceptional anode of potassium ion batteries (KIBs). The operando X-ray diffraction results, along with transmission electron microscopy and energy-dispersive X-ray spectroscopy mappings, successfully reveal the phase evolution of this material, which is (Bi,Sb)2S3 → (Bi,Sb) → K­(Bi,Sb) → K3(Bi,Sb) during the initial discharge and K3(Bi,Sb) → K­(Bi,Sb) → (Bi,Sb) in the charging process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
178
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(182 citation statements)
references
References 65 publications
4
178
0
Order By: Relevance
“…However, the large ionic radius (0.138 nm) of K + is prone to inducing sluggish reaction kinetics and structural collapse of electrodes upon electrochemical cycling. In this respect, tremendous efforts have been exerted to explore novel anode materials with high specific capacity, facile K‐ion uptake/release kinetics and structural robustness targeting high energy and long life KIBs …”
Section: Introductionmentioning
confidence: 99%
“…However, the large ionic radius (0.138 nm) of K + is prone to inducing sluggish reaction kinetics and structural collapse of electrodes upon electrochemical cycling. In this respect, tremendous efforts have been exerted to explore novel anode materials with high specific capacity, facile K‐ion uptake/release kinetics and structural robustness targeting high energy and long life KIBs …”
Section: Introductionmentioning
confidence: 99%
“…Alternative electrolytes with a new combination of salts and solvents, including high-salt-concentration electrolytes have been reported to improve the stability of K-based cells. [8][9][10][11][12][13][14][15][16][17][18] Among them, highly concentrated glyme-based electrolytes are the most versatile ones. For example, Xiao et al reported the highly concentrated KFSI 0.5 : glyme enabling reversible potassium plating/stripping with an efficiency of 99 %, thanks to the formation of an inorganic compound-rich, solid electrolyte interphase (SEI) on potassium metal.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium‐ion batteries (LIBs) have been rapidly developed since 1990s . Nowadays, portable electronic equipment, rapid development electric vehicle and state‐of‐the‐art smart grid are closely associated with LIBs due to their several advantages such as no memory effect, long cycle life and high energy density . However, LIBs using organic liquid electrolyte also have some unfavorable features including the leakage, highly volatile ability, and flammability of organic liquid electrolyte system and the growth of lithium dendrites, which may cause the degeneration of battery performance or even some unpredictable dangerous safety accidents .…”
Section: Introductionmentioning
confidence: 99%